The need for diagnostic criteria in systemic vasculitis - Suppiah, R; Robson, J; Basu, N; Luqmani, R (2011)
There are currently no diagnostic criteria for the systemic vasculitides. Due to the heterogeneous and non specific manner that vasculitis can present there is often a delay in diagnosis which translates to increase morbidity and mortality. The current disease definitions and classification criteria are often misapplied as diagnostic criteria, but evaluation of this has shown that they do not perform satisfactorily for this purpose. We discuss the CHCC definitions, the ACR classification criteria and the EMEA algorithm which is needed to bridge the inconsistency between the two. We also evaluate the FVSG proposal for polyarteritis nodosa, and attempts of the Behcet's disease community to develop diagnostic criteria. We provide a brief summary of how a diagnosis of vasculitis is currently made, describe how increased understanding of disease mechanisms has identified biomarkers which aid diagnosis, and describe how clinically applicable diagnostic criteria could be developed. © 2011 Bentham Science Publishers.